Interpretation of the Equine Leukogram - Satué, K.; Muñoz, A.; Gardón, J.C. (Journal of Hematology Research, 2014)
The systematic study of total number of leukocytes or white blood cells and their morphological characteristics offers valuable information for the diagnosis, prognosis, response to treatment and control of a wide variety of infectious or inflammatory disorders. This study provides a brief description of the physiological and morphological characteristics of the various types of leukocytes, including neutrophils, lymphocytes, eosinophils, monocytes and basophils and their quantitative and qualitative changes in response to diseases in the horse.